Bearing stresses in bolted composite joints with different contact interactions - Ahmad, Hilton (Engg Journals Publications, 2016)
In a bolted joint, it has been shown to be better to model the real contact between bolt and hole than to fix the boundary of the hole edge, a practice used by most previous researchers. Master-slave interaction was implemented in ABAQUS to simulate full contact conditions. Stress distributions were plotted along net-tension plane and hole boundary. Due to geometric non-linearity, the clearance and friction coefficients used substantially effected the maximum stress on hole boundary as shown using the benchmarking work of Eriksson. A physically-based constitutive model used is based on state-of-the art fracture mechanics was used for bolted joint strength prediction. Idealized models from Hollmann were remodelled both by fixing the hole boundary (following the original author) and by implementing full contact condition using CZM and XFEM. The physically-based constitutive law used independently measured of unnotched strength and fracture energy parameter for crack opening, which is calibrated from available literatures (known as apparent fracture energy). Good correlation with experimental results was found when using the real contact condition.